Economic, technical, and environmental viability of biodiesel blends derived from coffee waste. (March 2020) - Kamil, Mohammed; Ramadan, Khalid M.; Olabi, Abdul Ghani; Al-Ali, Eman I.; Ma, Xiao; Awad, Omar I.
Abstract: In this study we investigated the potential use of coffee waste feedstock in biodiesel production, considering economic viability, technical feasibility, and environmental compatibility. The investment potential for a small-scale biodiesel production facility (8000 t/y) was gauged by estimating relevant economic performance indicators. Biodiesel was then extracted from spent coffee grounds and blended with fossil diesel to develop four blends: B5, B10, B15, and B20. The conformity of this fuel with relevant standards (ASTM D6751 and ISO EN14214) was determined by characterizing and adjusting the fuel's properties during the production process. The technical and environmental performance of these blends was then tested in a single-cylinder compression ignition engine with an extended range of engine speeds under three engine loading conditions (100%, 75%, and 50%), using pure diesel fuel for benchmark comparisons. The evaluated economic metrics paint an optimistic picture of investment in this project. Waste coffee could result in improved economic performance over other feedstocks. Diesel fuel outperformed the biodiesel blends in terms of engine power, thermal efficiency, and fuel economy, whereas the blends were superior in terms of exhaust gas temperature; average exhaust gas temperature drops of 11 °C and 35.2 °C were measured under full load conditions for B5 and B20, respectively. All blends emitted lower levels of CO2, CO, and HC than did diesel, but higher NOx emissions were present, all proportional to the blend used. Our results clearly show that SCG has great potential as a feedstock for biodiesel production, given its derivation from existing waste materials, cleaner but comparable performance, and economically viable production. Highlights: Spent coffee grounds (SCG) are a potential feedstock for biodiesel production. SCG are an existing waste product requiring no further cultivation for fuel production. Economic analysis of an 8000 t/y plant indicated potential for financial viability. Technical analysis showed that SCG biodiesel performs comparably to regular diesel. Tailpipe emissions of CO, CO2, and HC were lower (NOx was higher) for SCG biodiesel.